Implementation Of The Systematic Land Registration Program (PTSL) at The Land Office of Bengkulu City - Tuti Handayani IS; Evi Lorita; Desti Rohmatullah (International Journal of Human Capital and Innovative Management, 2024)
The Systematic Land Registration Program (Pendaftaran Tanah Sistematis Lengkap/PTSL) was initiated by the Indonesian government to ensure legal certainty and protection of land ownership for all citizens. This study investigates the implementation of the PTSL program at the Land Office of Bengkulu City, highlighting its effectiveness, challenges, and impact on public administrative services. Employing a qualitative descriptive method, data were gathered through interviews, observations, and document analysis, guided by the theoretical framework of Edward III which emphasizes four key variables: communication, resources, disposition, and bureaucratic structure.The findings reveal that the implementation of the PTSL program in Bengkulu City is generally effective, supported by sufficient human and financial resources, clear communication strategies, and well-structured bureaucratic mechanisms. However, challenges such as complex administrative processes and public misconceptions about land registration procedures still persist. The research also documents the use of digital applications such as Sentuh Tanahku and Loketku, which have improved public access to land information and services. This study contributes to the field of public administration by providing empirical evidence on the role of systematic land registration in improving governance and legal certainty. It offers policy recommendations for optimizing land service delivery, particularly in urban areas with growing population pressures. The results are expected to inform future improvements in the national land certification strategy, especially in enhancing accessibility, transparency, and administrative efficiency